Efesiensi Penggunaan Bahan Bakar Pertamax (Octan 92) Pada Kendaraan Hemat Energi Di Politeknik Negeri Jember - Maulana, Fazeel; Kamil, M. Insan; Bayhaqi, Moch. Rifal (P3M Politeknik Negeri Jember, 2023)
At this time motorcycle users are increasing, the need for this means of transportation is very helpful for daily activities. With the importance of this means of transportation, people will choose motorbikes that have great power, are fuel efficient and are environmentally friendly. Many automotive fields are modifying or changing components such as standard coils replaced by racing coils so that the resulting combustion is greater and produces spark plugs larger and aims to get better performance. With better combustion, it is expected that the performance of an engine will definitely increase, one of which is from fuel consumption. The purpose of this study is to determine fuel efficiency on engine performance and then analyze specific fuel consumption on 4 stroke motorbikes. In this experiment, performance was tested to analyze the specific fuel consumption used in Pertamina's fuel production, namely Pertamax. This type of gasoline was tested on a Honda revo fit 110 cc motorbike using experimental. calculation of fuel consumption on the Argopuro vehicle car, namely 0.21 L/H